Digital Industrial Control Systems: Vulnerabilities and Security Technologies - Adeyanju*, Ibrahim Adepoju; Donald Emake, Erhovwosere; Olaniyan, Olatayo Moses; Omidiora, Elijah Olusayo; Adefarati, Temitope; Uzedhe, Godwin Obruozie; Okomba, Nnamdi Stephen (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
Digital Industrial Control Systems (ICS) are complex electromechanical systems composed of components such as sensors, actuators, programmable logic controllers and communication devices interconnected to perform monitoring and control tasks in different industries. ICS have many and varied applications in critical infrastructures across the globe. However, security is an important factor for any ICS operation. In recent times, there have been a myriad of security threats and attacks by malicious elements on ICS, which has become a concern to organizations and researchers. The development of internet and communication systems has also exacerbated such security concerns. Activities of these malicious elements on ICS can result in serious disasters in industrial environments, human casualties and financial loss. Every ICS network element should be protected to avoid threats, attacks and maintain safe reliable infrastructure. Research efforts have been dedicated to improve ICS security for several decades and are still ongoing. This paper reviews ICS threats, vulnerabilities, cyber-physical attacks and security technologies over the last two decades (2000-2019). Keywords: Industrial Control Systems; security; ICS; vulnerabilities; threats; cyber-attack; security technologies *Corresponding author: Tel.: +234 813 287 6689 E-mail: ibrahim.adeyanju@fuoye.edu.ng